Access to B-ISDN via PONs ATM communication in practice - Killat, Ulrich (Wiley ; Teubner, 1996)
"The development of Passive Optical Networks (PONs) and ATM for broadband applications represents the leading edge of telecommunications research. A comprehensive analysis of the latest research, this edited volume collates the expertise of international academics and researchers to describe one of the most advanced communications systems developed on a multinational basis." "This highly topical reference will be of value to all telecommunications professionals engaged in systems development at the conceptual or implementation level. The accessible approach will also appeal to researchers in academia and industry in the fields of networking, optical communications, electronics and computer science."--BOOK JACKET.